Promoting Discussions About Diversity in the Language Classroom: Digital Storytelling as an Exploratory Case Study - Somayeh Kamranian (Journal of Teaching and Learning)
Digital storytelling is a narrative technique that combines audio, video and animation elements. It can be used to provide opportunities for the promotion of cultural understanding in the university language classroom. In this study, pedagogy that combines digital storytelling techniques and computational technologies are explored, as part of language studies that can allow instructors to create an intercultural experience. The outcomes of an undergraduate learning exercise have been evaluated, along with this researcher’s experience as an instructor who used digital storytelling in a French-as-a-second-language classroom, and includes these students’ solicited feedback. In this case study, a group of students conducted internet research to explore the online cultural diversity and cultural differences of Francophone culture. They then created digital stories to represent this diversity. The findings have been analysed to evaluate the potential place of inclusivity and diversity tools in French-as-a-second-language learning, and to share the potential of this practical pedagogy approach for other university educators.